2023
DOI: 10.1073/pnas.2301170120
|View full text |Cite
|
Sign up to set email alerts
|

Molecular responses during bacterial filamentation reveal inhibition methods of drug-resistant bacteria

Abstract: Bacterial antimicrobial resistance (AMR) is among the most significant challenges to current human society. Exposing bacteria to antibiotics can activate their self-saving responses, e.g., filamentation, leading to the development of bacterial AMR. Understanding the molecular changes during the self-saving responses can reveal new inhibition methods of drug-resistant bacteria. Herein, we used an online microfluidics mass spectrometry system for real-time characterization of metabolic changes of bacteria during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…The activity of most DGCs/PDEs depends not only on GGDEF or EAL/HD‐GYP domains but also on signal input via an N‐terminal sensory domain 15 , 131 , 132 . Internal and external cues stimulate the N‐terminal sensory domain of DGCs and PDEs to initiate the enzyme activities that control intracellular c‐di‐GMP levels 9 , 131 , 132 , 133 , 134 . In conclusion, different signals control intracellular c‐di‐GMP levels via different DGCs/PDEs.…”
Section: Comparison Of C‐di‐gmp and Camp Regulatory Modelsmentioning
confidence: 99%
“…The activity of most DGCs/PDEs depends not only on GGDEF or EAL/HD‐GYP domains but also on signal input via an N‐terminal sensory domain 15 , 131 , 132 . Internal and external cues stimulate the N‐terminal sensory domain of DGCs and PDEs to initiate the enzyme activities that control intracellular c‐di‐GMP levels 9 , 131 , 132 , 133 , 134 . In conclusion, different signals control intracellular c‐di‐GMP levels via different DGCs/PDEs.…”
Section: Comparison Of C‐di‐gmp and Camp Regulatory Modelsmentioning
confidence: 99%
“…In particular, people living in developing countries are easily infected with multidrug-resistant microorganisms due to poor health services and the abuse of antibiotics. Even in the United States, the number of infections caused by antibiotic-resistant bacteria climbed from 2 million to 2.8 million within 6 years (i.e., 2013–2019). , Moreover, the USA alone spends $25 billion/year to manage chronic wounds that are associated with high rates of morbidity and mortality. Pseudomonas aeruginosa ( P. aeruginosa ), a drug-resistant Gram-negative pathogen, can clinically cause acute or chronic infections, being one of the top-listed pathogens for hospital-acquired infections. Treatment of P. aeruginosa infection is extremely difficult because of its rapid mutations and adaptation to gain resistance to antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is an urgent need to investigate the mechanism of antibiotic resistance in microbes. Studies reveal that metabolic reprogramming mediates antibiotic efficacy [7][8][9][10][11][12][13][14]. A metabolomic approach based on gas chromatography-mass spectrometry showed that glucose and alanine contents were decreased in kanamycin-resistant Edwardsiella tarda [15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies reveal that metabolic reprogramming mediates antibiotic efficacy [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. A metabolomic approach based on gas chromatography–mass spectrometry showed that glucose and alanine contents were decreased in kanamycin-resistant Edwardsiella tarda [ 15 ].…”
Section: Introductionmentioning
confidence: 99%